Exercise training improves circulatory dynamics in adolescents with postural orthostatic tachycardia syndrome - Yanagimoto, Yoshitoki; Ishizaki, Yuko; Terashima, Toshiki; Yoshida, Ryuhei; Ishitani, Kento; Haraguchi, Kohei; Yamamoto, Mana; Kubota, Mayumi; Adomi, Yuto; Yamasaki, Shinobu; Suga, Toshimitsu; Kaneko, Kazunari (Frontiers in Pediatrics, 2025)
IntroductionExercise training is recommended for PoTS; however, very few studies have examined the effectiveness of exercise training in young adolescents with PoTS. We evaluated the effects of ergometer endurance exercise on the circulatory dynamics of children with PoTS using cardiopulmonary exercise (CPX) testing, standing tests, and cardiac output monitoring.MethodsOverall, 28 participants with PoTS (19 males) aged 12–15 years were admitted to the Department of Pediatrics, Kansai Medical University General Medical Center, for 1 month between August 2020 and November 2023. Of the participants, 17 were assigned to the exercise group (13 boys) and 11 were assigned to the control group (6 boys). All participants underwent the standing test and CPX testing upon admission. The exercise group performed ergometer exercise for 30 min once per day, five times per week for 4 weeks. After 4 weeks, both groups completed the standing and CPX tests again. During the standing test, the patients underwent non-invasive hemodynamic monitoring using the AESCULON Mini®.ResultsThere were no significant differences between the two groups in demographic characteristics at admission (before the start of exercise training). Stroke volume, cardiac output, cardiac index, and thoracic fluid content increased after exercise training in the exercise group [pre- vs. post-exercise: cardiac output (ml) 61.7 vs. 73.1 (P = 0.009); cardiac output (L/min): 6.6 vs. 7.7 (P = 0.001); cardiac index (L/min/m2): 4.3 vs. 5.0 (P = 0.029); thoracic fluid content: 28.7 vs. 33.8 (P = 0.001)]. Exercise duration and maximal oxygen uptake (VO2) increased after exercise training in the exercise group on CPX testing [pre- vs. post-exercise: load time (min): 1.8 vs. 9.6 (P = 0.002), peak VO2 (ml/min/kg): 30.3 vs. 33.2 (P = 0.005)]. The hemodynamic and CPX test results were unchanged in the control group. No significant changes were observed in orthostatic test results in either group.DiscussionEndurance exercise training for 4 weeks increased cardiac output during orthostasis in children with PoTS and inhibited the downward migration of blood. We conclude that ergometer exercise training for 4 weeks in young adolescents with PoTS may improve circulatory dynamics during orthostasis.